PENERAPAN METODE COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN KETERAMPILAN KERJASAMA SISWA DALAM PEMBELAJARAN SEJARAH - Pitria Apriyani (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2016)
It became the benchmark for researchers to improve learning condition in class XI IPS 3 of SMA Negeri 1 Rajagaluh. The researcher conducted classroom action with using cooperative learning method, STAD type to improve student’s collaboration skill in class XI IPS 3 of SMA Negeri 1 Rajagaluh. This research used Classroom Action Research (CAR). The procedure or design of this research used Kemmis and M.C Taggart research design starting for planning, implementation, observation and reflection. Research data was obtained through documentation and observational study. This research consisted of foeur cycles and four acts. The research result obtained by researcher indicated that the application of cooperative learning method, STAD type in learning history can improve student’s collaboration skill in learning history in Class XI IPS 3 of SMA Negeri 1 Rajagaluh, it can be seen from the data obtained from predetermined indicators that the student’s are able to use the deal, bearing responsibility, appreciating the contribution, respecting individual differences and collecting the assignments on time according to the assessment criteria of each determined indicator.